The railway panopticon: State formation, carceral power, and everyday policing in the late-nineteenth-century train station. (August 2022) - Nowak, Zachary
Abstract: Historical scholarship on the formation of the state in the United States has focused on the national and state governments and has searched for state power in courtrooms, barracks, and legislative chambers. This article reveals the growth of municipal state power in an unlikely place: the large urban train station, a crucial transportation chokepoint. Using nineteenth-century St. Louis as my primary example, I focus on how both police and non-state actors took advantage of an emergent place of constricted mobility. Rather than imprison people to punish criminality, subalterns caught in the railway panopticon were disciplined according to then-prevailing gender and racial norms. I argue that the intersection of networks there created a place where local police and their allies could surveil, check, and potentially stop more people than in any other place in the urban landscape. This article refocuses the history of state building on a more prosaic location than the halls of government and traces the history of police as enforcers of the racial norms and patriarchal order. Central railway stations became, unintentionally, key sites of state formation and carceral power. This research reveals the spatial heterogeneity of the state's strength, provides a genealogy for contemporary racially inequitable policing, and creates a framework to investigate other places where state and non-state actors can exercise particular power over everyday people. Graphical abstract: Image 1 Highlights: Large urban train stations were a 19th-century transportation bottleneck. Multiple rail lines, huge numbers of passengers, and few exits enabled mass surveillance. A small number of police officers—working with police matrons, railway employees, and reporters—could surveil and potentially stop many people. The station police often arrested movement of women and people of color. There may be other analogous, everyday places of state formation in similar chokepoints.